Petrology and geochemistry of the back-arc lithospheric mantle beneath eastern Payunia (La Pampa, Argentina): evidence from Agua Poca peridotite xenoliths - Bertotto, Gustavo Walter (2013)
This paper presents the results of new petrochemical studies carried out on mantle xenoliths hosted in Pleistocene basaltic rocks from the Agua Poca volcano in central-western Argentina. Mantle xenoliths studied are shown to be mainly anhydrous spinel lherzolites with minor amounts of harzburgite and banded pyroxenite, showing highly variable equilibrium temperatures ranging from 820°C to 1030°C at 1.0 to 2.0 GPa. This constitutes evidence that the mantle xenoliths are representative of a large portion of the lithospheric mantle column and that the geothermal gradient is not very elevated as reported in some other Patagonian provinces. Geochemical characteristics of clinopyroxene in the mantle xenoliths allow classification into two groups; Groups 1 and 2. Group 1 contains most of the lherzolites and has light-REE depletion, with slightly positive anomalies of Eu in some samples and extreme Nb and Ta depletion. Group 2 consists of two harzburgitic samples, has flat REE patterns with lower Sm to Lu concentrations, with enriched Sr and negative HFSE anomalies. Based on mineral and residua compositions estimated assuming equilibrium with clinopyroxenes, Group 1 can be considered to be refractory residua after up to 7%, non-modal, near-fractional melting of a spinel-facies Primitive Mantle. Group 2 can be considered to be after ca. 13% of partial melting. It is inferred that partial melting events in the lithospheric mantle beneath the Agua Poca occurred in different ages since the Proterozoic, but compared with Group 1, the metasomatic overprint is dominant in Group 2 mantle xenoliths. The calculated melt compositions from Group 2 are interpreted to be transient liquid compositions developed during melt-peridotite interaction, and are different from the host alkaline basalts. The HFSE-depleted composition estimated for the rising melt suggests the presence of a slab-derived component, although the possibility cannot be disregarded (on the basis of present data) that such a geochemical feature is due to segregation of HFSE-bearing minerals during the interaction with the peridotite. Thus, we attribute the metasomatic agent to a basaltic melt and to a minor amount of slab-derived fluids.